Aggression in children: unravelling the interplay of genes and environment through (epi)genetics and metabolomics - Dorret I. Boomsma (Journal of Pediatric and Neonatal Individualized Medicine, 2015)
Aggression inflicts a huge burden on affected children, their families, and society. Estimates for the prevalence of clinical aggression in children range between 2 and 16%, and childhood aggression tends to continue into adulthood. Current psychological treatments and pharmacological interventions are not effective for all children with aggressive behaviors and there is a huge need for more personalized approaches, which requires insight into the heterogeneity and the mechanisms underlying aggression and its associated comorbidities. Here we discuss what is currently known with regard to individual differences in childhood aggression. Studies employing new opportunities in large scale genotyping, epigenetics and metabolomics technology will in future help to explain heterogeneity and highlight pathways from molecule to phenotype. The FP7-ACTION project (Aggression in Children: Unravelling gene-environment interplay to inform Treatment and InterventiON strategies) aims to contribute to knowledge that will help children, their families, teachers and society at large.